Arabidopsis U2AF65 Regulates Flowering Time and the Growth of Pollen Tubes - Park, Hyo-Young; Lee, Hee Tae; Lee, Jeong Hwan; Kim, Jeong-Kook (Frontiers in Plant Science, 2019)
During pre-mRNA splicing, U2 small nuclear ribonucleoprotein auxiliary factor 65 (U2AF65) interacts with U2AF35 and splicing factor 1 (SF1), allowing for the recognition of the 3'-splice site by the ternary complex. The functional characterization of U2AF65 homologs has not been performed in Arabidopsis thaliana yet. Here, we show that normal plant development, including floral transition and male gametophyte development, requires two Arabidopsis U2AF65 isoforms (AtU2AF65a and AtU2AF65b). Loss-of-function mutants of these two isoforms displayed opposite flowering phenotypes: atu2af65a mutants showed late flowering, whereas atu2af65b mutants were characterized by slightly early flowering, as compared to that in the wild-type (Col-0) plants. These abnormal flowering phenotypes were well-correlated with the expression patterns of the flowering time genes such as FLOWERING LOCUS C (FLC) and FLOWERING LOCUS T (FT). However, the two atu2af65 mutants did not display any morphological abnormalities or alterations in abiotic stress tests. Double mutation of the AtU2AF65a and AtU2AF65b genes resulted in non-viable seeds due to defective male gametophyte. In vitro pollen germination test revealed that mutations in both AtU2AF65a and AtU2AF65b genes significantly impaired pollen tube growth. Collectively, our findings suggest that two protein isoforms of AtU2AF65 are differentially involved in regulating flowering time and display a redundant role in pollen tube growth.